High bio-content photocurable coatings for wood surfaces derived from itaconic acid - YILDIZ, ZEHRA (My University, 2023)
Surface coatings are used extensively in many industrial areas, especially in furniture and machine coatings in order to extend the lifespan of the end product. For wood surfaces, it is important to protect the surface from external factors by maintaining the texture and colour of the surface. The conventional wood coatings require the usage of water or solvent; thus they have the risk of fiber swelling from the cellulosic wood material resulting deformation on the wood surface. Photocuring is favoured compared to the conventional solvent/water based thermal curing techniques due to the requirement of none/less water/solvent, rapid curing mechanism in just a few seconds/minutes, curing ability at lower temperatures with an effective curing rates. Soybean oil is a good candidate to be used as an alternative to the petrochemicals as being renewable, cheap, non-toxic, and abundant. It has five unsaturated groups on its backbone that is suitable to react furtherly with various chemical compounds to be used in polymer design. Itaconic acid (IA) is one of the high-value-added bio-chemicals of US Energy Department which is being manufactured by the fermentation of citric acid. In this study, epoxidized soybean oil (ESBO) was reacted by IA in order to obtain a high bio-content photocurable oligomer. The scheme of the oligomer can be seen in Figure 1. The synthesized ESBO-IA oligomer was characterized by Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (1H NMR) spectroscopies, respectively then were included in coating formulations together with various types of reactive diluents and photo initiator. The coating formulations were applied on chipboard wood surfaces by using a roller and cured by UV-light. The coated surfaces were characterized by means of abrasion resistance (Taber) and solvent resistance tests, respectively
Keywords: Photocuring; Soybean Oil; Itaconic Acid; Chipboard; Wood Coating